Acute mountain sickness in a subject with metabolic syndrome at high altitude - Strapazzon, G.; Cogo, A.; Semplicini, A. (High Altitude Medicine & Biology, 2008)
Visitors at high altitude are increasing in age and comorbidities, which can lead to a failure in acclimatization. We describe the development of acute mountain sickness (AMS) in a 44-year-old man with metabolic syndrome and the time- and altitude-dependent correlation between the development of AMS and blood pressure and heart rate changes. Our observations support a dominant role of endothelial dysfunction in the pathogenesis of AMS and suggest new behavioral indications.